EFFECT OF MEDICAL NUTRITION KNOWLEDGE ON GLYCEMIC REGULATION IN PATIENTS WITH DIABETES MELLITUS - Bita Motamedıan; Gülşah Yenidünya Yalın (Sabiad)
Objective: To evaluate the effect of medical nutrition knowledge on glycemic control in patients with Diabetes mellitus (DM).Material and Methods: Type 1 and Type 2 DM patients (n: 105) who had received medical nutrition therapy (MNT) education at least once were recruited. Nutritional knowledge scores (NKS) were obtained from the NKS evaluation form and patients were classified into Group 1 (NKS ≤60, n:24) and Group 2 (NKS>60, n:81). Patients’ socio-demographic characteristics, biochemical parameters, nutritional habits, anthropometric measurements, and 24-hour food consumption data were recruited.Results: Mean age in Group 1 and Group 2 was 50.5±12.1 and 45.5±15.5, respectively. Mean NKS scores were higher in patients with type 1 DM (p=0.02). There was no significant relation between NKS and HbA1c (p=0.3). NKS was significantly associated with higher educational degrees, higher HDL, and lower frequency of neuropathy (p=0.03; 0.01; 0.01, respectively). NKS was negatively correlated with age, triglyceride, and neuropathy frequency (p=0.001, r=-0.35, p=0.004, r=-0.36; p=0.01, r=-0.24, respectively); positively correlated with HDL, educational degree, health literacy and presence of leisure time activities (p<0.001, r=0.38; p<0.001, r=0.53; p=0.01, r=0.26 and p<0.001, r=0.31, respectively). Logistic regression analysis revealed the relationship between NKS and educational degree (p=0.01, OR:0.17, CI:0.04-0.68).Conclusion: Adequacy of nutritional knowledge may not be sufficient in achieving better glycemic regulation in DM and patients should be motivated to reflect their nutritional knowledge in their daily living activities.